Basic Refinery Training Courseware in Enhancing Technical Employees’ Visualization Skills - Yaacob, Norarbaiyah; Ali, Dayana Farzeeha; Abdullah, Abdul Halim; Mohd Zaid, Norasykin; Mokhtar, Mahani; Ibrahim, Nor Hasniza (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Various research has been conducted to enhance the employees’ visualization skills in different areas and the importance and the role of visualization skills towards the employee’s achievement, especially in the industry such as manufacturing, medical, oil and gas field, and many more. To improve visualization skills, the use of effective training methods and tools should be applied to facilitate and enhance the understanding and performance in general, in a way to help them solve problems at the workplace. Thus, the aim of this paper focuses to the attention on the practical use of augmented reality (AR) with the ability of digital mobile application in the crude oil refinery process within the oil and gas industry environment, describing the potential and the effectiveness of the technology to enhance the visualization skill among the technical employees. This study used Basic refinery courseware that can be accessed via digital network to give an interactive training experience that can enhance technical employees’ visualization skills. This courseware shows the positive effect and impact on technical employees’ visualization skills and performance based on the results. The results have also shown an increased motivation, making them more cooperative and developing visualization skills more quickly. Considering these results, it can be concluded that Basic Refinery training courseware based on augmented reality application is an effective and beneficial tool to be applied in training programs among the workplace’s technical employees.